Associations between cardiac fibrosis and permanent atrial fibrillation in advanced heart failure - Aldhoon, B; Kučera, T; Smorodinová, N; Martínek, J; Melenovský, V; Kautzner, J (Physiological research, 2013)
Atrial fibrosis is considered as the basis in the development of long-standing atrial fibrillation (AF). However, in advanced heart failure (HF), the independent role of fibrosis for AF development is less clear since HF itself leads to atrial scarring. Our study aimed to differentiate patients with AF from patients without AF in a population consisting of patients with advanced HF. Myocardial samples from the right atrial and the left ventricular wall were obtained during heart transplantation from the explanted hearts of 21 male patients with advanced HF. Long-standing AF was present in 10 of them and the remaining 11 patients served as sinus rhythm controls. Echocardiographic and hemodynamic measurements were recorded prior to heart transplantation. Collagen volume fraction (CVF), transforming growth factor-beta (TGF-beta), and connective tissue growth factor (CTGF) expression in myocardial specimens were assessed histologically and immunohistochemically. The groups were well matched according to age (51.9+/-8.8 vs. 51.3+/-9.3 y) and co-morbidities. The AF group had higher blood pressure in the right atrium (13.6+/-7.7 vs. 6.0+/-5.0 mmHg; p=0.02), larger left atrium diameter (56.1+/-7.7 vs. 50+/-5.1 mm; p=0.043), higher left atrium wall stress (18.1+/-2.1 vs. 16.1+/-1.7 kdynes/m(2); p=0.04), and longer duration of HF (5.0+/-2.9 vs. 2.0+/-1.6 y, p=0.008). There were no significant differences in CVF (p=0.12), in CTGF (p=0.60), and in TGF-beta expression (p=0.66) in the atrial myocardium between the two study groups. In conclusions, in advanced HF, atrial fibrosis expressed by CVF is invariably present regardless of occurrence of AF. In addition to atrial wall fibrosis, increased wall stress might contribute to AF development in long-standing AF.
Keywords: Collagen; krevní tlak; lidé; Middle Aged; Endomyocardial Fibrosis; Heart Failure; diferenciální diagnóza; stárnutí; Blood Pressure; srdeční selhání; Atrial Fibrillation; Transforming Growth Factor beta; Humans; srdeční síně; transformující růstový faktor beta; kolagen; lidé středního věku; mužské pohlaví; endomyokardiální fibróza; srdeční frekvence; Heart Atria; Aging; Diagnosis, Differential; Male; fibrilace síní; Heart Rate